Alteridad 2.0: textualidades audiovisuales y autorrepresentación a través de las redes sociales online de un emprendimiento artístico familiar de Ayacucho, Perú. El caso de una joven artista conocida como Renata Flores Rivera. Una aproximación desde la etnografía audiovisual - Escalante Euán, David Alberto (2024)
This research corresponds to the written and theoretical part of an ethnographic audiovisual work and is inscribed in the context of COVID19 in Lima and Ayacucho, Peru during 2020 and 2021. This work analyzes the audiovisual representations of an artistic and entrepreneur family articulated by a young woman from Ayacucho, Peru, known as Renata Flores Rivera. The research reformulates previous artistic and journalistic approaches that emphasize the work of an individual subject and proposes an anthropological perspective that reflects on family relationships and the confessionality of the research subjects through their online social networks. The research suggests understanding a family artistic entrepreneurship project that is in the process of learning about representation and self-representation through images and sounds in the online world, but is dependent on and affected by narratives that pertain to the offline world. It also addresses the fragility of local, regional and national institutions close to neoliberalism and that for multiple reasons cannot articulate to provide all human rights to their community, which is evidenced by the effects of the COVID19 pandemic. The implications of the audiovisual production of the subjects are reviewed as audiovisual textualities, within a theory of cultural control, as corporealities that are enunciated from the contemporary recording devices envolved in these social processes.